From Easter to Holy Week: the paschal mystery and liturgical renewal in the twentieth century - Moore, Laura E. (Anglican-Episcopal theology and history, 2019)
"The story of the twentieth-century Liturgical Movement is, more than anything else, about the rediscovery and renewed understanding of the fundamental reality of the Paschal Mystery and of the Paschal identity of the Church. This identity is expressed and celebrated whenever the Body of Christ - every member - welcomes new members in the waters of baptism and feasts with them in the Eucharist, especially as these are celebrated during Holy Week. This book explores this rediscovery, first in the Roman Catholic Church and then in the Episcopal Church and other Churches of the Anglican Communion, and looks in particular at how both grassroots and official work played a role in renewing and restoring the liturgical celebrations of Holy Week"--